Implementasi Media Pembelajaran Bahan Alam Pada Anak PAUD Usia 5-6 Tahun - Eni, Eni; Darmiyanti, Astuti; Rochimah, Nur (Jurnal Ilmiah Wahana Pendidikan, 2025)
Several factors that hinder early childhood learning, including the lack of facilities available in schools, the lack of teachers' ability to organize interesting lessons and the lack of use of natural media in the learning process are the background to this research. This is because teachers prefer to use practical media such as books, worksheets, pictures and paper, so children often feel bored when studying. One of the learning media that can be used by teachers is natural material media. This media is not only interesting, but is also considered effective and cheap. Thus, this research aims to explain how to implement natural media in early childhood learning, especially children aged five to six years. There are several techniques used, namely literature review and data collection techniques which involve collecting and reviewing relevant sources such as books, articles and journals.